1988
DOI: 10.1128/iai.56.2.413-418.1988
|View full text |Cite
|
Sign up to set email alerts
|

Differences in excretion and efficiency of the aerobactin and enterochelin siderophores in a bovine pathogenic strain of Escherichia coli

Abstract: Secretion of aerobactin is thought to play an important part in the virulence of invasive Escherichia coli also capable of synthesizing enterochelin. Why, despite its markedly lower affinity for iron than that of enterochelin, aerobactin proves to be the' predominant active siderophore for bacterial growth in transferrin was investigated. We studied the action of two iron chelators, 2,2'-dipyridyl and transferrin, in expression of the aerobactin and enterochelin genes. Specifically, we describe the sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Bovine E. coli producing the CS31A antigen have been reported in Japan [16] although the fimbriae observed on these strains appear to be different from those described by Girardeau et al [51. Although the role of CS31A and F165 in virulence has not been demonstrated, these surface antigens seem to be mainly associated with E. cob strains from cases of septicemia. Experimental infection of calves with CS31A-positive E. coli produced septicemia [61 and genetic studies have shown that CS31A-positive non-ETEC possess antibiotic resistance plasmids encoding for both CS31A and aerobactin, the latter of which is a virulence factor [17]. Among 0115 E. coli, only those with F165 antigen induced septicemia in piglets [3].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine E. coli producing the CS31A antigen have been reported in Japan [16] although the fimbriae observed on these strains appear to be different from those described by Girardeau et al [51. Although the role of CS31A and F165 in virulence has not been demonstrated, these surface antigens seem to be mainly associated with E. cob strains from cases of septicemia. Experimental infection of calves with CS31A-positive E. coli produced septicemia [61 and genetic studies have shown that CS31A-positive non-ETEC possess antibiotic resistance plasmids encoding for both CS31A and aerobactin, the latter of which is a virulence factor [17]. Among 0115 E. coli, only those with F165 antigen induced septicemia in piglets [3].…”
Section: Discussionmentioning
confidence: 99%
“…(6) Cohcin production was measured by the agar overlay method [15] using E. coil K12 D B6433 as the susceptible strain and a mutant of E. coil K12 D B6433 resistant to col V [16] for identifying colicin V. (7) Aerobactin production was identified using the hydroxamate assay of Csaky [17] according to Der Vartanian [18]. (8) Antibiotic resistances were studied using the disk diffusion method [15].…”
Section: Methodsmentioning
confidence: 99%
“…
One hundred Escherichia coil isolates from human septicemia were characterized ,~,,ith respect to O serogroups 1,2,4, 6,7,8, 15,18, 75 and 78, a-hemolysin, carboxylesterase B typing, cytotoxic necrotizing factor, F163 and CS31A fimbrial antigens, aerobactin production, colicins, and antibiotic sensitivity. A factorial analysis of correspondence and X-" tests indicated that most of E. coli isolates belonging to the studied O serogroups were positive for the virulence factors or markers a-haemolysin, carboxylesterase B 2 type, cytotoxic necrotizing factor, F165 fimbrial antigen and were antibiotic-sensitive (Group I).
…”
mentioning
confidence: 99%
“…Although anaerobically grown E. coli cells are able to use enterochelin-Fe 3 + complexes as their iron source [8,17], efficient enterochelin production is accomplished only in extreme iron-poor conditions which are probably never reached in the anaerobic large intestine [18]. In accordance with this, Der Vartanian et al [19] were not able to find enterochelin in the intestinal contents of gnotobiotic lambs challenged with aerobactin-and enterochelin-producing E. coli.…”
Section: Resultsmentioning
confidence: 99%